PENATALAKSANAAN PERSIAPAN PASIEN PREOPERATIF DI RUMAH SAKIT UMUM DAERAH KABUPATEN CIAMIS - Aap Apipudin; Heni Marliany; Arif Nandang (Jurnal Ilmiah Kesehatan Keperawatan, 2017)
Procedure preoperative actions in some hospitals have developed such reference to the needs of patients who will do the surgery. This procedure is expected to become a paramedic guidelines in an effort to prepare the patient preoperatively, so the preoperative preparation can be done well. The purpose of this study is find a picture of the management of the patient's preoperative preparation in hospital.This research use descriptive research. The population in this study were surgical patients in the General Hospital of Ciamis. The sampling technique by means of quota sampling a total sample of 30 people.It is known that the management of physical preparation in the patient's preoperative 83.3% implemented, supporting the management of the patient's preoperative preparation 100% implemented, preparation Management informed consent on the patient's preoperative 100% implemented and management of mental preparation / psychic on the patient's preoperative 100% implemented. The overall results showed that the majority of the category held as many as 25 people (83.3%) Keywords: Management, Preoperative